2019
DOI: 10.1289/ehp4599
|View full text |Cite
|
Sign up to set email alerts
|

Oral Systemic Bioavailability of Bisphenol A and Bisphenol S in Pigs

Abstract: Background:Given its hormonal activity, bisphenol S (BPS) as a substitute for bisphenol A (BPA) could actually increase the risk of endocrine disruption if its toxicokinetic (TK) properties, namely its oral availability and systemic persistency, were higher than those of BPA.Objectives:The TK behavior of BPA and BPS was investigated by administering the two compounds by intravenous and oral routes in piglet, a known valid model for investigating oral TK.Methods:Experiments were conducted in piglets to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 44 publications
6
46
0
1
Order By: Relevance
“…Synthetic compounds like bisphenol A (BPA) are omnipresent in food packaging, and BPA in particular has been shown to act as a xenohormone with the potential to impair reproductive function in men and increase cancer risk ( 19 ). While some manufacturers have responded to the public's concerns about BPA exposure by switching to bisphenol S (BPS), research indicates that this alternative may actually be more readily absorbed into the body ( 27 ). Phthalates are another class of synthetic chemicals commonly used in food packaging, and like BPA and BPS, they have the potential to act as xenohormones.…”
Section: Concerns Surrounding the Intake Of Ultra-processed Foodsmentioning
confidence: 99%
“…Synthetic compounds like bisphenol A (BPA) are omnipresent in food packaging, and BPA in particular has been shown to act as a xenohormone with the potential to impair reproductive function in men and increase cancer risk ( 19 ). While some manufacturers have responded to the public's concerns about BPA exposure by switching to bisphenol S (BPS), research indicates that this alternative may actually be more readily absorbed into the body ( 27 ). Phthalates are another class of synthetic chemicals commonly used in food packaging, and like BPA and BPS, they have the potential to act as xenohormones.…”
Section: Concerns Surrounding the Intake Of Ultra-processed Foodsmentioning
confidence: 99%
“…In humans, BPA, BPS and BPF cross the placenta and represent a risk for the foetus [ 11 ]. BPA exposure during perinatal period is associated with non-communicable diseases (NCDs) at childhood and adulthood [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, the bioavailability of BPS substitutes might be higher than for BPA. A recent study conducted in pigs, an ideal model for mimicking the human digestive tract, demonstrated the lower plasma clearance of BPS (3.5 lower) compared to BPA and an increased oral systemic exposure exceeding 250-fold [168]. These observations draw our attention and raise concerns about replacing BPA by BPS, as this may result in an increased internal exposure to EDCs.…”
Section: Resultsmentioning
confidence: 92%